A Facile Route to Backbone‐Tethered N‐Heterocyclic Carbene (NHC) Ligands via NHC to aNHC Rearrangement in NHC Silicon Halide Adducts. Issue 7 (22nd December 2014) - Schneider, Heidi; Schmidt, David; Radius, Udo
Abstract The reaction of 1, 3‐diisopropylimidazolin‐2‐ylidene (iPr2Im) with diphenyldichlorosilane (Ph2SiCl2) leads to the adduct (iPr2Im)SiCl2Ph21. Prolonged heating of isolated 1 at 66 °C in THF affords the backbone‐tethered bis(imidazolium) salt [(aHiPr2Im)2SiPh2]2+ 2 Cl−2 ("a" denotes "abnormal" coordination of the NHC), which can be synthesized in high yields in one step starting from two equivalents of iPr2Im and Ph2SiCl2. Imidazolium salt 2 can be deprotonated in THF at room temperature using sodium hydride as a base and catalytic amounts of sodium tert‐butoxide to give the stable N‐heterocyclic dicarbene (aiPr2Im)2SiPh23, in which two NHCs are backbone‐tethered with a SiPh2 group. This easy‐to‐synthesize dicarbene 3 can be used as a novel ligand type in transition metal chemistry for the preparation of dinuclear NHC complexes, as exemplified by the synthesis of the homodinuclear copper(I) complex [{a(ClCuiPr2Im)}2SiPh2] 4.